Language and humor: Arabic-English translation errors in bilingual memes - Muassomah, Muassomah; Yurisa, Penny Respati; Hakim, Arief Rahman (Universitas Dian Nuswantoro, 2025)
Translation is not just a transition between different languages, but a transfer and transformation of meaning and form between different cultures. This study aims to analyze translation errors in the landscape of bilingual information in the form of memes, as well as explore the translation errors that result in cuteness and humor. This study uses a qualitative approach with the data source of memes from websites containing Arabic-English bilingual information. The data were analyzed using error analysis and through informative discourse analysis. The research findings show that the bilingual information memes have shown translation failures namely literal translation errors, loss of context and meaning, misinterpretation and lack of contextual explanation. This study concludes that the translation failures that occur give rise to cuteness and a sense of humor.